Genotype-Guided Dosing of Warfarin in Chinese Adults: A Multicenter Randomized Clinical Trial. (August 2020) - Guo, Chengxian; Kuang, Yun; Zhou, Honghao; Yuan, Hong; Pei, Qi; Li, Jingle; Jiang, Weihong; Ng, Chee M.; Chen, Xiaoping; Huo, Yong; Cui, Yimin; Wang, Xiaobin; et al.
Abstract : Background: Warfarin is an effective treatment for thromboembolic disease but has a narrow therapeutic index; optimal anticoagulation dosage can differ tremendously among individuals. We aimed to evaluate whether genotype-guided warfarin dosing is superior to routine clinical dosing for the outcomes of interest in Chinese patients. Methods: We conducted a multicenter, randomized, single-blind, parallel-controlled trial from September 2014 to April 2017 in 15 hospitals in China. Eligible patients were ≥18 years of age, with atrial fibrillation or deep vein thrombosis without previous treatment of warfarin or a bleeding disorder. Nine follow-up visits were performed during the 12-week study period. The primary outcome measure was the percentage of time in the therapeutic range of the international normalized ratio during the first 12 weeks after starting warfarin therapy. Results: A total of 660 participants were enrolled and randomly assigned to a genotype-guided dosing group or a control group under standard dosing. The genotype-guided dosing group had a significantly higher percentage of time in the therapeutic range than the control group (58.8% versus 53.2% [95% CI of group difference, 1.1–10.2]; P =0.01). The genotype-guided dosing group also achieved the target international normalized ratio sooner than the control group. In subgroup analyses, warfarin normal sensitivity group had an even higher percentage of time in the therapeutic range during the first 12 weeks compared with the control group (60.8% versus 48.9% [95% CI, 1.1–24.4]). The incidence of adverse events was low in both groups. Conclusions: The outcomes of genotype-guided warfarin dosing were superior to those of clinical standard dosing. These findings raise the prospect of precision warfarin treatment in China. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02211326. Abstract : Supplemental Digital Content is available in the text.